Assessment of the feed additive consisting of l‐cystine for all animal species for the renewal of its authorisation (Bretagne Chimie Fine [BCF Life Sciences]) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for the renewal of the authorisation of l‐cystine as nutritional feed additive. The additive is authorised for use in all animal species (3c391). The applicant has provided evidence that the additive currently in the market complies with the existing conditions of authorisation. The EFSA Panel on Additives and Products or Substances used in Animal Feed concluded that the use of the feed additive in animal nutrition remains safe for the target species, the consumers and the environment. As regards the safety for the user, l‐cystine is not an irritant to skin or eyes and is not a skin sensitiser. Exposure by inhalation of persons handling the additive cannot be excluded. The present application for the renewal of the authorisation does not include any modification proposal that would have an impact on the efficacy of the additive and therefore there is no need for reassessing the efficacy.